1994
DOI: 10.1177/107769909407100415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organizational Size on Job Satisfaction of Top Editors at U.S. Dailies

Abstract: Drawing on social system and referencegroup theory, this study hypothesized that topeditors at large newspapers would bemoresatisfied with their jobs than top editors at small newspapers. Editors on larger newspapers were expected to be more satisfied because increased role specialization gives themgreaterautonomy, their salariesare higher, and their jobs are more prestigious. A national probability sample of top editors at daily newspapers in the United States supports the hypotheses that editors at larger ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
0
11
0
4
Order By: Relevance
“…Demers also reports that journalists at corporate newspapers are more satisfied with their jobs because they have more autonomy, status, and prestige than journalists at noncorporate or entrepreneurial newspapers (Demers, 1993(Demers, , 1994a(Demers, , 1995. Furthermore, as organizations become more corporatized, editorials and letters to the editor published in them become more, not less, critical of mainstream groups and ideas (Demers, 1996b), and established news sources (mayors and police chiefs) in communities served by corporate newspapers also believe that those newspapers are more critical of their policies and city hall (Demers, 1998c).…”
Section: Empirical Research On Corporate Newspapersmentioning
confidence: 97%
“…Demers also reports that journalists at corporate newspapers are more satisfied with their jobs because they have more autonomy, status, and prestige than journalists at noncorporate or entrepreneurial newspapers (Demers, 1993(Demers, , 1994a(Demers, , 1995. Furthermore, as organizations become more corporatized, editorials and letters to the editor published in them become more, not less, critical of mainstream groups and ideas (Demers, 1996b), and established news sources (mayors and police chiefs) in communities served by corporate newspapers also believe that those newspapers are more critical of their policies and city hall (Demers, 1998c).…”
Section: Empirical Research On Corporate Newspapersmentioning
confidence: 97%
“…Along with role perceptions, journalists' demographic characteristics can affect attitudes, opinions, and news content. Demers (1994) found that older newspaper editors were more satisfied with their jobs, while Knobloch-Westerwick et al (2008) showed that a journalist's race can affect which stories are selected and which stories a journalist reads. Gender, in particular, has the potential to affect attitudes toward contextual journalism.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Only one direct measure of actual profitability was employed, and no content measures of quality were used. More research needs to be done to examine the effects of corporate structure on content, organizational routines and practices, and on job satisfaction and autonomy (Demers, 1993(Demers, , 1994a. Nevertheless, the findings do support a growing body of research that suggests that corporate newspapers, even though they are more profitable, place more emphasis on quality and other goals.…”
Section: Summary and Discussionmentioning
confidence: 51%